Impact of an Upper Respiratory Tract Infection on Botulinum Toxin Efficacy in Spasmodic Dysphonia Patients. (11th September 2019) - Kirke, Diana N.; Kaye, Rachel; Blitzer, Andrew
Abstract : Objective: To determine whether the presence of a concomitant upper respiratory tract infection (URI) impacts upon Botulinum toxin (BoNT) efficacy in spasmodic dysphonia (SD) patients. Study Design: Case series and literature review. Methods: All SD patients with a concurrent URI, presenting for BoNT therapy at a clinical research center from November 2016 to December 2017 were included. A total of 12 patients were identified. Patients were followed for at least two BoNT treatment cycles (approximately 6 months). The primary outcome measure was efficacy of the initial BoNT injection and the secondary outcome measure was the efficacy of the subsequent BoNT injection. Results: All subjects had adductor type SD (ADSD). There were 10 females and two males with a median age of 55 years (±19.5). All patients were well established on a consistent BoNT treatment regime, with an average administered dose of 1.0 unit (range 0.2–1.80 units). Bilateral injections were administered to 10 patients. Regarding the primary outcome measure, five failed to have any response to BoNT (41.7%), four had a partial response (33.3%), and three had a positive response to treatment (25.0%). When patients had their follow‐up injection in the absence of URI symptoms, 11 patients had a positive response to treatment (91.7%). Conclusion: While the interplay between illness and BoNT efficacy is yet to be elucidated, we report that some patients are affected. We recommend that SD patients presenting for BoNT administration with a concomitant URI, should be counseled that their treatment might have decreased effect. Level of Evidence: 4 Laryngoscope, 130:1746–1749, 2020